Titanium material and method for producing the same

By forming an oxidation coating with specific element content on the surface of the titanium material, the problem of insufficient weather resistance of titanium material under severe acidic environments and high temperature conditions is solved, and high weather resistance and whiteness are achieved.

CN116133765BActive Publication Date: 2025-04-15NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180062490.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-16
Filing Date
2021-09-14
Publication Date
2025-04-15
Estimated Expiration
2041-09-14

AI Technical Summary

Technical Problem

The existing titanium materials are insufficient in severe acidic environments, especially in high temperature conditions.

Method used

By forming an oxidation coating containing specific elements on the surface of the titanium material, the specific method includes controlling the element content of the oxidation coating using a cleaning process of nitric acid-hydrofluoric acid, ensuring that the surface contains Zn: 0.1 atomic % or more, Ca: 0.5 atomic % or more, C: 20.0 atomic % or less, and F: 5.0 atomic % or less in the surface oxidation coating.

Benefits of technology

It realizes high weather resistance of titanium materials in harsh acidic environments, and takes into account the improvement of whiteness. It is suitable for building materials used in acidic environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004121313940000141
    Figure BDA0004121313940000141
  • Figure BDA0004121313940000171
    Figure BDA0004121313940000171
Patent Text Reader

Abstract

The titanium material is characterized in that, when the chemical composition of the surface is analyzed by X-ray photoelectron spectroscopy, the surface composition contains Zn: 0.1 atomic % or more, and Ca: 0.5 atomic % or more, and the composition of the surface oxide film is C: 20.0 atomic % or less, and F: 5.0 atomic % or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a titanium material and a method for producing a titanium material. This application claims priority based on Japanese Patent Application No. 2020-155144 filed in Japan on September 16, 2020, and the contents are incorporated herein by reference. Background Art

[0002] Titanium materials used in building materials such as walls and roofs of buildings (titanium materials for building materials) are roughly divided into: non-coloring materials that show silver, which is the color of titanium itself; and coloring materials that give design characteristics by giving a certain degree of thickness of oxide film on the surface through anodization to show interference colors such as red or blue.

[0003] Titanium is used as a building material in coastal areas where salt is deposited due to its excellent corrosion resistance. It has been more than 20 years since titanium began to be used as a building material, but there have been no reports of problematic corrosion. Both non-coloring materials and coloring materials show excellent corrosion resistance.

[0004] When non-coloring materials and coloring materials are exposed to the atmosphere for a long time, there is a possibility of discoloration. It is clear that the discoloration is caused by the interference color caused by the increase of the oxide film on the surface of the titanium material to a thickness of several tens of nanometers due to an acidic environment of pH 4.5 or below, such as acid rain. This oxide film of several tens of nanometers does not damage the corrosion resistance of titanium. However, in areas such as the walls or roofs of buildings where appearance is important, titanium materials, especially non-coloring materials, are required that are not easy to produce interference colors caused by the increase in the thickness of the oxide film, and such titanium materials are being developed.

[0005] For example, Patent Document 1 discloses a titanium material that is less likely to discolor in an atmospheric environment, characterized in that the average carbon concentration within a range of 100 nm from the outermost surface is 14 atomic % or less, and the outermost surface has an oxide film with a thickness of 12 to 40 nm.

[0006] Patent Document 2 discloses a titanium material that is less likely to discolor, wherein the amount of fluorine in an oxide film on the surface is 7 atomic % or less.

[0007] Patent Document 3 discloses a titanium material that is not easily discolored in an atmospheric environment, wherein the composition of the titanium oxide in the oxide film formed on the titanium surface and present in the range of 3 nm from the titanium surface is set to TiO x When x is in the range of 0.8 to 1.8, and the density of the oxide film is 4.2 g / cm 3 The titanium material disclosed in Patent Document 3 is produced by treating the titanium surface with a mixed solution of nitric acid and hydrofluoric acid and then treating it with a nitric acid solution.

[0008] Patent document 4 discloses a pure titanium material for building materials, characterized in that it is a pure titanium material for building materials, wherein Fe as an impurity element is suppressed to less than 0.08 mass %, Nb is suppressed to less than 0.02 mass %, and Co is suppressed to less than 0.02 mass %. The titanium material disclosed in Patent document 4 is manufactured by heating at 130 to 280° C. for a predetermined time in the atmosphere or in a vacuum after pickling treatment in the final process.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2002-12962

[0012] Patent Document 2: Japanese Patent Application Publication No. 2002-47589

[0013] Patent Document 3: Japanese Patent Application Publication No. 2005-154882

[0014] Patent Document 4: Japanese Patent Application Publication No. 2004-300569 Summary of the invention

[0015] Problem that the invention aims to solve

[0016] The non-coloring material is required to have high weather resistance without generating interference color. Furthermore, in recent years, with the change of the atmospheric environment leading to the rise of temperature, a titanium material that is not easily discolored even in an acidic environment of pH 3.0 or less, which is more severe than the above, is required.

[0017] In Patent Documents 1 to 4, the evaluation of weather resistance is as follows. After being immersed in a sulfuric acid aqueous solution of pH 3 to 4 at 60°C for several days, the weather resistance is evaluated based on the color difference before and after the immersion. It is also recorded that the color difference is 3 to 7 or less when immersed in a sulfuric acid aqueous solution of pH 3 at 60°C for 7 days or 14 days, and the color difference is less than 5 and further less than 1 when immersed in a sulfuric acid aqueous solution of pH 4 at 60°C for 3 days. However, the above evaluation of weather resistance cannot fully reflect the use in a high temperature environment. In addition, for the titanium materials described in Patent Documents 1 to 4, when immersed in a sulfuric acid aqueous solution of pH 4 at 80°C for 4 days, the color difference before and after the immersion is about 15 or more, and the existing titanium materials do not have sufficient weather resistance under higher temperature conditions.

[0018] That is, it is difficult for existing titanium materials to achieve weather resistance in a severe acidic environment.

[0019] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a titanium material having excellent weather resistance and a method for efficiently producing the titanium material.

[0020] Solutions for solving problems

[0021] The present inventors have conducted a detailed study on the relationship between the surface oxide film formed on the titanium material and the weather resistance, and found that the weather resistance is excellent when the surface oxide film contains specific elements. In addition, the present inventors have found that the element content of the surface oxide film can be controlled by using a nitric acid-hydrofluoric acid cleaning process. Further, it is newly found that by implementing the above cleaning process in the final process, weather resistance in an acidic environment can be obtained. The present inventors have conducted further research based on the insights obtained, and as a result, the present invention has been completed.

[0022] The gist of the present invention completed based on the above findings is as follows.

[0023] [1] A titanium material according to one embodiment of the present invention is characterized in that, when the chemical composition of the surface is analyzed by X-ray photoelectron spectroscopy, the composition of the surface contains Zn: 0.1 atomic % or more and Ca: 0.5 atomic % or more, and the composition of the surface oxide film contains C: 20.0 atomic % or less and F: 5.0 atomic % or less.

[0024] [2] The titanium material according to [1] above, wherein the thickness of the surface oxide film may be 5 to 20 nm.

[0025] [3] In addition, another embodiment of the present invention involves a method for manufacturing a titanium material having a cleaning step for cleaning a titanium blank, the cleaning step comprising: an immersion treatment, immersing the titanium blank in an aqueous solution at a temperature of 40 to 60°C for more than 1.0 minute, the aqueous solution containing a zinc salt: 0.00030 to 0.65000 mass % in terms of Zn, a calcium salt: 0.00060 to 0.40000 mass % in terms of Ca, HF: 1.0 to 6.0 mass %, and HNO3: 4.0 to 10.0 mass %; and a water washing treatment, washing the titanium blank taken out from the aqueous solution with water.

[0026] [4] In the method for producing a titanium material described in [3] above, the zinc salt may be present in an amount of 0.00030 to 0.00100 mass % in terms of Zn, and the calcium salt may be present in an amount of 0.00060 to 0.00108 mass % in terms of Ca.

[0027] [5] In the method for producing a titanium material described in [3] or [4] above, the zinc salt may be ZnCl2.

[0028] [6] In the method for producing a titanium material described in [3] or [4] above, the calcium salt may be CaCl2.

[0029] [7] In the method for manufacturing a titanium material described in [5] above, the calcium salt may be CaCl2.

[0030] [8] The method for producing a titanium material described in [3] or [4] may further include a heating step of heating the titanium blank after the cleaning step to 300 to 900° C. in an inert atmosphere.

[0031] [9] The method for producing a titanium material described in [5] above may further include a heating step of heating the titanium material after the cleaning step to 300 to 900° C. in an inert atmosphere.

[0032]

[10] The method for producing a titanium material described in [6] above may further include a heating step of heating the titanium material after the cleaning step to 300 to 900° C. in an inert atmosphere.

[0033]

[11] The method for producing a titanium material described in [7] above may further include a heating step of heating the titanium blank after the cleaning step to 300 to 900° C. in an inert atmosphere.

[0034] Effects of the Invention

[0035] As described above, according to the present invention, a titanium material having excellent weather resistance and a method for efficiently producing the titanium material can be provided. DETAILED DESCRIPTION

[0036] Hereinafter, preferred embodiments of the present invention will be described in detail. The description will be made in the following order.

[0037] <1. Titanium>

[0038] <2. Titanium material manufacturing method>

[0039] It should be noted that, in the numerical ranges described below including "to", the ranges include the lower limit and the upper limit. In the numerical values ​​expressed as "less than" or "greater than", the numerical values ​​are not included in the numerical range.

[0040] <1. Titanium>

[0041] The titanium material according to the present embodiment includes a titanium main body material (titanium base material) and a surface oxide film disposed on the surface of the titanium main body material. The titanium material according to the present embodiment will be described in detail below.

[0042] The titanium main body material in the titanium material of the present embodiment may be composed of pure titanium or a titanium alloy. The titanium main body material is, for example, pure titanium or a titanium alloy having a Ti content of 70 mass % or more.

[0043] Pure titanium includes, for example, Grade 1 to Grade 4 of the JIS standard and industrial pure titanium specified in Grade 1 to Grade 4 of the corresponding ASTM standard. That is, in this embodiment, the industrial pure titanium used as the object is C: 0.1% or less, H: 0.015% or less, O: 0.4% or less, N: 0.07% or less, Fe: 0.5% or less, and the balance includes Ti and impurities. It should be noted that in buildings, industrial pure titanium specified in JIS Grade 1 or ASTM Gr. 1, which is equivalent thereto, or its equivalent materials are mainly used.

[0044] Examples of the titanium alloy include α-type titanium alloy, α+β-type titanium alloy, and β-type titanium alloy.

[0045] As α-type titanium alloys, for example, include high corrosion-resistant alloys (titanium alloys specified in Grades 11 to 13, 17, 19 to 22 of JIS standards, and Grades 7, 11, 13, 14, 17, 30, and 31 of ASTM standards, or titanium alloys further containing small amounts of various elements), Ti-0.5Cu, Ti-1.0Cu, Ti-1.0Cu-0.5Nb, Ti-1.0Cu-1.0Sn-0.3Si-0.25Nb, Ti-0.05~0.2Pd, etc.

[0046] Examples of the α+β type titanium alloy include Ti-3Al-2.5V, Ti-5Al-1Fe, and Ti-6Al-4V.

[0047] Examples of the β-type titanium alloy include Ti-11.5Mo-6Zr-4.5Sn, Ti-8V-3Al-6Cr-4Mo-4Zr, Ti-13V-11Cr-3Al, Ti-15V-3Al-3Cr-3Sn, Ti-20V-4Al-1Sn, and Ti-22V-4Al.

[0048] In the titanium material involved in this embodiment, when the chemical composition of the surface of the titanium material is analyzed by X-ray photoelectron spectroscopy, the composition of the surface is Zn: 0.1 atomic % or more, and Ca: 0.5 atomic % or more, and the composition of the surface oxide film is C: 20.0 atomic % or less, and F: 5.0 atomic % or less.

[0049] [When the chemical composition of the surface was analyzed by X-ray photoelectron spectroscopy, the surface composition was Zn: 0.1 atomic % or more, Ca: 0.5 atomic % or more]

[0050] In the titanium material involved in the present embodiment, when the chemical composition of the surface of the titanium material is analyzed by X-ray photoelectron spectroscopy, the surface Zn content is more than 0.1 atomic % and the Ca content is more than 0.5 atomic %. The Zn and Ca on the surface of the titanium material improve the weather resistance of the titanium material. Although its mechanism is not very clear, the inventors speculate that it is caused by any one or more effects of the inhibitor effect of Zn and Ca, the oxygen deficiency repair effect or the bipolar membrane effect. The inhibitor effect is an effect that suppresses the dissolution of titanium by preferentially dissolving the Zn and Ca on the surface of the titanium material in an acid rain environment, thereby suppressing the growth of the surface oxide film. The oxygen deficiency repair effect is an effect that suppresses the growth of the surface oxide film by preferentially dissolving the TiO2 that constitutes the surface oxide film. 4+ Zn doping 2+ and Ca 2+ , repairing oxygen deficiencies, and as a result, inhibiting the dissolution of titanium and the growth of the surface oxide film. The bipolar film effect is the effect of the precipitation of oxides (ZnO, CaO) with different semiconductor properties from TiO2, which hinder the movement of electrons from the acidic solution attached to the surface of the surface oxide film and inhibit the growth of the surface oxide film.

[0051] When the chemical composition of the surface of the titanium material is analyzed by X-ray photoelectron spectroscopy, if the Zn content on the surface of the titanium material is 0.1 atomic % or more and the Ca content is 0.5 atomic % or more, the weather resistance of the titanium material is improved by any one or more of the above effects. The Zn content is preferably 0.1 atomic % or more, 0.2 atomic % or more, and more preferably 0.3 atomic % or more. The Ca content is preferably 0.5 atomic % or more, 0.6 atomic % or more, and more preferably 0.7 atomic % or more. Furthermore, it is preferred that the Zn content is 1.0 atomic % or less and the Ca content is 1.5 atomic % or less. When the Zn content and the Ca content are higher than these values, the above effects show a tendency to saturation. The Zn content is more preferably 0.9 atomic % or less. The Ca content is more preferably 1.4 atomic % or less, and further preferably 1.3 atomic % or less.

[0052] [C: 20.0 atomic % or less, F: 5.0 atomic % or less]

[0053] The C content and F content in the surface oxide film are less than 20.0 atomic % and less than 5.0 atomic %, respectively. When the C content and F content of the surface oxide film are high, discoloration is likely to occur. This is because carbon or fluorine or their compounds reduce the effect of the surface oxide film that inhibits the dissolution of the titanium substrate, making titanium easy to dissolve, or exist in the surface oxide film in the form of a compound with titanium, which is easy to dissolve, thereby causing the surface oxide film to grow. Here, in addition to existing alone, carbon and fluorine in the surface oxide film also have the possibility of existing in the form of a compound with titanium and hydrogen, oxygen, etc. If the C content is less than 20.0 atomic % and the F content is less than 5.0 atomic %, the dissolution of titanium in the above-mentioned titanium material and the growth of the surface oxide film can be suppressed. Preferably, the C content is less than 18.0 atomic %, less than 15.0 atomic %, or less than 6.0 atomic %. The F content is less than 4.9 atomic %, less than 4.8 atomic %, less than 4.5 atomic %, or less than 4.0 atomic %.

[0054] The C content and F content of the surface oxide film are preferably small, but in production, the C content is substantially 0.5 atomic % or more and the F content is substantially 1.0 atomic % or more. More preferably, the C content is 1.0 atomic % or more and the F content is more preferably 2.0 atomic % or more.

[0055] [Thickness of surface oxide film: 5 to 20 nm]

[0056] The thickness of the surface oxide film can be set to, for example, less than 100 nm, but more preferably less than 80 nm, and more preferably more than 5 nm and less than 20 nm. If the thickness of the surface oxide film is less than 20 nm, the generation of interference colors caused by the surface oxide film can be suppressed. The thickness of the surface oxide film is more preferably less than 18 nm, and more preferably less than 12 nm.

[0057] On the other hand, the lower limit of the thickness of the surface oxide film is preferably 5 nm or more. If the thickness of the surface oxide film is 5 nm or more, the dissolution of Ti contained in the titanium material can be suppressed, and higher weather resistance can be obtained. The thickness of the surface oxide film is more preferably 6 nm or more.

[0058] In addition, here, the thickness of the surface oxide film refers to the position from the surface of the surface oxide film to the position where the oxygen concentration is the middle concentration between the maximum concentration and the basic concentration. It should be noted that the basic concentration refers to the average oxygen concentration in the range where the oxygen concentration curve becomes flat in the range where the oxygen concentration is less than 5 atomic %, while performing XPS analysis from the surface of the titanium material along the depth direction while sputtering. The flatness mentioned here refers to the quantitative value of the oxygen concentration measured by the XPS analysis described later, which contains at most 5 points, and the slope of the approximate straight line in a certain arbitrary depth range is less than 0.002 in absolute value. The formula of the above approximate straight line is calculated by the least squares method.

[0059] The content of Zn and the content of Ca, the content of F and the content of C of the surface oxide film, and the thickness of the surface oxide film can be obtained by the titanium material immersed in acetone after ultrasonic cleaning, according to the composition distribution in the depth direction from the surface obtained by XPS. The ultrasonic cleaning time is, for example, more than 30 seconds. In the determination of the content of Zn and the content of Ca, after the element is determined to exist by qualitative analysis by XPS, the quantitative analysis value of each element is obtained, which is used as the content of Zn and the content of Ca. The content of Zn and the content of Ca mentioned here refer to the respective contents of the range of less than 8nm from the surface of the sample under the state of not implementing sputtering. The composition analysis in the depth direction is calculated with SiO2, and the quantitative analysis of each element is carried out every 2nm sputtering depth, from the surface of the titanium material to the depth at which the oxygen concentration reaches the basic concentration, the content of F, the content of C and the content of O are obtained. The thickness of the surface oxide film is set to the following value, and XPS analysis is performed until the depth of the baseline at which the oxygen concentration curve becomes flat in the range of oxygen concentration below 5 atomic % can be obtained, and the sputtering time at the position where the O content is halved relative to the maximum value is obtained, and the sputtering rate converted in SiO2 is multiplied by the above sputtering time. The sputtering rate converted in SiO2 refers to the sputtering rate when the SiO2 film whose thickness has been measured in advance using an ellipsometer is obtained under the same measurement conditions. It should be noted that, usually, the baseline can be obtained by analyzing to a position 50nm from the surface, but depending on the surface state of the titanium material, it is sometimes necessary to analyze to a position 100nm from the surface to obtain the baseline.

[0060] The maximum fluorine concentration in the surface oxide film measured by the above method is taken as the F content in the surface oxide film. In addition, since the surface of the titanium material is sometimes affected by the attachment of organic matter, for carbon whose concentration decreases approximately monotonically with respect to the depth direction, the portion where the oxygen concentration decreases near the surface of the titanium material is considered to be the influence of the attached organic matter, and the maximum value of the carbon concentration after the depth where the oxygen concentration in the surface oxide film reaches the maximum value is taken as the C content.

[0061] The shape of the titanium material according to the present embodiment is not particularly limited, and may be a plate, a coil, a strip, etc. So far, the titanium material according to the present embodiment has been described.

[0062] [Whiteness]

[0063] In recent years, from the perspective of design, in the non-coloring material, the material with high whiteness is also required. As a method for efficiently obtaining the titanium material with a high surface of whiteness, there is a pickling finishing process such as nitric acid-hydrofluoric acid pickling using nitric acid-hydrofluoric acid. It is believed that by pickling, fine concavo-convex is formed on the titanium surface, and diffuse reflection occurs due to the fine concavo-convex, so that the whiteness of the titanium material improves. In order to obtain high whiteness, it is necessary to maintain the titanium material of the pickled surface without rolling or heat treatment after pickling to make a product. But, if the titanium material maintaining the pickled surface is exposed to the atmosphere for a long time, discoloration sometimes occurs. It is believed that this is due to a large amount of oxygen defects in the oxide film formed after pickling, and therefore the dissolution of Ti ions in the atmosphere cannot be prevented.

[0064] That is, in the above-mentioned conventional pickling finishing, although the whiteness can be improved, the discoloration in an acidic environment is significant. Therefore, it is difficult for existing titanium materials to achieve both weather resistance and whiteness in a severe acidic environment.

[0065] The present inventors have found that by performing a cleaning step including the above-mentioned immersion treatment using nitric acid-hydrofluoric acid in the final step, a titanium material having both weather resistance and whiteness in an acidic environment can be provided.

[0066] Furthermore, the whiteness L of the surface of the titanium material * It is preferably 70 or more. Thus, both weather resistance and a high whiteness which is preferred from the perspective of design can be taken into account. However, when the whiteness is too high, due to excessive formation of fine surface irregularities, sea salt particles or pollutant particles adhere to the surface, and the possibility of corrosion starting points increases, and there is also the possibility of corrosion resistance deterioration. Therefore, L * It is preferably 90 or less. Furthermore, it is preferred that L * It is not more than 80. It should be noted that this whiteness can be easily achieved by the washing step described later.

[0067] Whiteness is measured, for example, by the following method. That is, according to JIS Z8730:2009, L is measured using a colorimeter CR-200b manufactured by Konica Minolta and light source C. * , evaluate the whiteness.

[0068] <2. Titanium material manufacturing method>

[0069] In the manufacturing method of the titanium material involved in the present embodiment, the cleaning process is implemented as the last process in the manufacturing process of the titanium material. In the manufacturing method of the titanium material involved in the present embodiment, for example, after the casting process, hot rolling process, cold rolling process, annealing process, and temper rolling / stretching straightening process are sequentially implemented, the cleaning process is implemented. In addition, for example, when the temper rolling / stretching straightening process is omitted, the cleaning process is performed after the annealing process. The above processes except the cleaning process can be performed by a known method.

[0070] For example, in the ingot casting process, sponge titanium or a master alloy for adding alloying elements is used as a raw material, and various melting methods such as vacuum arc melting, electron beam melting, or plasma melting are used to produce an ingot of pure titanium or titanium alloy having the above composition. Then, the obtained ingot is divided into blocks as needed and hot forged into ingots.

[0071] In the hot rolling process, for example, the ingot is heated to 600-850°C and rolled at a temperature below the phase transformation point. The reduction rate can be determined according to the characteristics of the final product. The heating temperature is preferably 700-850°C. From the perspective of deformation resistance, the lower limit of the heating temperature is preferably above 700°C. As for the upper limit of the heating temperature, since the thickness of the oxide film of the titanium billet after hot rolling can be thinned, the descaling after hot rolling can be performed under mild conditions, it is preferably below 850°C.

[0072] In the cold rolling process, the hot-rolled titanium billet may be rolled under conditions that allow the desired thickness or properties to be obtained. In the case of multiple cold rolling passes, the titanium billet may be annealed between the cold rolling passes.

[0073] In the annealing process after the cold rolling process, for example, the titanium blank may be annealed in an inert atmosphere after removing impurities such as lubricating oil attached in the cold rolling process in an alkali cleaning line. In addition, for example, the titanium blank after the cold rolling process may be subjected to atmospheric annealing, salt bath descaling, and pickling in sequence.

[0074] The temper rolling / stretch straightening step is intended to correct the shape of the titanium billet after the annealing step, for example, and may be appropriately performed.

[0075] The cleaning process includes: an immersion treatment, immersing the titanium billet in an aqueous solution at a temperature of 40 to 60°C for more than 1.0 minute, wherein the aqueous solution contains zinc salt: 0.00030 to 0.65000 mass % converted to Zn, calcium salt: 0.00060 to 0.40000 mass % converted to Ca, HF: 1.0 to 6.0 mass % and HNO3: 4.0 to 10.0 mass %; and a water washing treatment, washing the titanium billet taken out from the aqueous solution with water.

[0076] More preferably, the cleaning process includes: an immersion treatment, immersing the titanium billet in an aqueous solution at a temperature of 40 to 60°C for more than 1.0 minute, the aqueous solution containing zinc salt: 0.00030 to 0.00100 mass % calculated as Zn, calcium salt: 0.00060 to 0.00108 mass % calculated as Ca, HF: 1.0 to 6.0 mass % and HNO3: 4.0 to 10.0 mass %; and a water washing treatment, washing the titanium billet taken out from the aqueous solution with water.

[0077] The aqueous solution used in the immersion treatment contains 0.00030 to 0.65000 mass % of a zinc salt in terms of Zn. Examples of zinc salts include ZnCl2, ZnSO4, Zn(NO3)2, Zn3(PO4)2, and ZnCO3. Among them, ZnCl2 is preferred because it has the highest solubility in water.

[0078] The content of the zinc salt is 0.00030 to 0.65000 mass % in terms of Zn. When the content of the zinc salt is less than 0.00030 mass % in terms of Zn, zinc oxides that can suppress the growth of the surface oxide film will not be formed on the surface of the titanium material as the final product, and thus the weather resistance becomes poor.

[0079] From the viewpoint of solubility of the zinc salt and stable production of the surface oxide film, the upper limit of the zinc salt is 0.65000 mass % or less in terms of Zn.

[0080] The content of zinc salt is preferably converted to below 0.00150 mass % with Zn, and when the content of zinc salt is converted to greater than 0.00100 mass % with Zn, although weather resistance is good, zinc oxide formed on the surface oxide film sometimes gathers. Due to the gathered zinc oxide, the titanium material surface becomes uneven, so sometimes uneven color is produced on the titanium material surface, and designability becomes a problem and cannot be used in building materials. If the content of zinc salt is converted to below 0.00100 mass % with Zn, uneven color can be suppressed. Therefore, the content of zinc salt is more preferably converted to below 0.00100 mass %, below 0.00080 mass % with Zn. The content of zinc salt is preferably converted to more than 0.00060 mass % with Zn.

[0081] The aqueous solution used in the immersion treatment contains 0.00060 to 0.40000 mass % of a calcium salt in terms of Ca. Examples of the calcium salt include CaCl2, CaSO4, Ca(NO3)2, and CaCO3. Among them, CaCl2 is preferred due to its high solubility in water and low deliquescent properties.

[0082] The content of the calcium salt is 0.00060 to 0.40000% by mass in terms of Ca. When the content of the calcium salt is less than 0.00060% by mass in terms of Ca, calcium oxides that can suppress the growth of the surface oxide film will not be formed on the surface of the titanium material as the final product, and thus the weather resistance becomes poor.

[0083] On the other hand, from the perspective of the solubility of calcium salt and the stable manufacture of surface oxide film, the upper limit of calcium salt is 0.40000 mass %. The content of calcium salt can be converted to 0.00200 mass % or less with Ca. In addition, when the content of calcium salt is greater than 0.00108 mass % with Ca, calcium oxide sometimes aggregates like zinc oxide. Due to the aggregated calcium oxide, the titanium material surface becomes uneven, so sometimes uneven color is produced on the titanium material surface, and design becomes a problem. If the content of calcium salt is converted to 0.00108 mass % or less with Ca, uneven color can be suppressed. Therefore, the content of calcium salt is preferably converted to 0.00108 mass % or less with Ca, and more preferably 0.00100 mass % or less. In addition, the content of calcium salt is preferably converted to 0.00072 mass % or more with Ca. It should be noted that in the area where zinc oxide and calcium oxide aggregated on the surface of titanium material exist, high O concentration can be detected by XPS. Therefore, when zinc oxide and calcium oxide are aggregated, the value of the thickness of the surface oxide film obtained by the above method becomes large.

[0084] The aqueous solution used in the immersion treatment contains HF: 1.0 to 6.0 mass% and HNO3: 4.0 to 10.0 mass%. If the aqueous solution used in the cleaning process contains HF: 1.0 to 6.0 mass% and HNO3: 4.0 to 10.0 mass%, fine concavoconvexity is formed on the surface of the titanium material. The HF content is preferably 5.0 mass% or less. The HNO3 content is preferably 8.0 mass% or less. In addition, the HF content is preferably 1.5 mass% or more. The HNO3 content is preferably 4.5 mass% or more.

[0085] The temperature of the aqueous solution is 40 to 60°C. When the temperature of the aqueous solution is less than 40°C, the titanium material is not pickled uniformly, and sometimes the color of the titanium material surface is uneven. On the other hand, when the temperature of the aqueous solution is greater than 60°C, HNO3 smoke is generated, which has an adverse effect on the manufacturing equipment. Therefore, the temperature of the aqueous solution is 40 to 60°C. The temperature of the aqueous solution is preferably 50°C or less.

[0086] The immersion time is 1.0 minutes or more. If the immersion time is 1.0 minutes or more, fine concavo-convex will be formed on the surface of the titanium material, and there will be no color unevenness. On the other hand, the upper limit of the immersion time is not particularly limited, and is preferably 2.0 minutes or less. If the immersion time is 2.0 minutes or less, the treatment can be carried out while maintaining the productivity of the continuous production line.

[0087] Through the above immersion treatment, Zn in the aqueous solution 2+ and Ca 2+ Adsorbed on the surface of titanium blank.

[0088] After the immersion treatment, the titanium blank is washed with water. The washing method is not particularly limited, and water washing can be performed by immersion in a water bath or spray washing. By washing with water, the excess aqueous solution on the surface of the titanium blank can be removed, and a surface oxide film can be formed on the surface of the titanium blank. At this time, Zn adsorbed on the surface of the titanium blank can be formed. 2+ and Ca 2+ of oxides.

[0089] After the cleaning process, the titanium material involved in the present embodiment can be manufactured, but in order to further reduce the F content of the surface oxide film, it is preferred to heat the titanium blank after the cleaning process to 300-900° C. in an inert atmosphere as needed. By heating the titanium blank after the cleaning process to 300-900° C. in an inert atmosphere, the fluorotitanate ions mixed in the surface oxide film are decomposed by heating, and F is discharged outside the surface oxide film, so that the F content in the surface oxide film can be reduced. The inert atmosphere is, for example, a vacuum atmosphere, an argon atmosphere, or a helium atmosphere.

[0090] It should be noted that the vacuum atmosphere mentioned here refers to a vacuum degree of 7.0×10 -4 ~2.5×10 -2 The argon atmosphere refers to an atmosphere containing 90% by volume or more of argon gas, and the helium atmosphere refers to an atmosphere containing 90% by volume or more of helium gas.

[0091] The heating time is preferably 0.5 to 10.0 hours. If the heating time is within the above range, the fluorotitanic acid mixed in the surface oxide film during the immersion treatment can be fully decomposed. The lower limit of the heating time is more preferably 1.0 hour, and the upper limit of the heating time is more preferably 5.0 hours.

[0092] For the titanium material manufactured through the above-mentioned cleaning process, an example of the results of qualitative and quantitative analysis of the titanium material surface by XPS is shown. Table 1 is an example of the quantitative analysis results based on XPS of the surface of the titanium material involved in this embodiment and an example of the quantitative analysis results based on XPS of the surface of a general titanium material. It should be noted that the "-" in Table 1 indicates that it is below the detection limit.

[0093] [Table 1]

[0094] element Material of the present invention Existing Materials Ca(atomic%) 0.7 0.2 Zn(atomic%) 0.3 -

[0095] As shown in Table 1, in the titanium material according to the present embodiment, the Zn content is 0.3 atomic %, and the Ca content is 0.7 atomic %, which are increased compared with the conventional material.

[0096] The above is the description of the method for producing the titanium material according to the present embodiment.

[0097] Example

[0098] The following examples are provided to specifically describe the embodiments of the present invention. It should be noted that the following examples are merely examples of the present invention, and the present invention is not limited to the following examples.

[0099] (Example 1)

[0100] Titanium cold-rolled sheets (titanium substrates) of the types shown in Table 2 were manufactured, and a plurality of samples of various sizes were cut out from the cold-rolled sheets, and immersion treatment was performed under the conditions shown in Table 2. The immersion treatment conditions are shown in Table 2. Next, the immersion-treated cold-rolled sheets were washed with water according to the following method. That is, the immersion-treated cold-rolled sheets were immersed in a water bath at room temperature (25° C.) for 1 minute to remove the pickling solution on the surface.

[0101] No. 1 in Table 2 is an example in which the cleaning process is not performed (an example in which cold rolling annealing is maintained), and No. 2 is an example in which the aqueous solution used in the immersion treatment in the cleaning process does not contain zinc salt and calcium salt. It should be noted that CP1 shown in the titanium billet variety column in Table 2 represents industrial pure titanium JIS 1 grade, CP2 represents industrial pure titanium JIS 2 grade, and CP3 represents industrial pure titanium JIS 3 grade. It should be noted that the underlined conditions in Table 2 represent conditions outside the scope of the present invention.

[0102] [Table 2]

[0103]

[0104] The sample surface after washing with water and immersion in acetone for 60 seconds for ultrasonic cleaning was subjected to qualitative and quantitative analysis of the surface composition and depth analysis by XPS. The analysis conditions based on XPS are as follows.

[0105] Device: VersaProbeIII manufactured by ULVAC-PHI, Inc.

[0106] X-ray source: mono-AlKα (hν: 1486.6 eV)

[0107] Beam diameter: 200μmΦ (≒Analysis area)

[0108] Detection depth: 2~8nm

[0109] Sputtering conditions: Ar +, sputtering rate 2.0nm / min. (SiO2 conversion value)

[0110] The SiO2 conversion value refers to the sputtering rate obtained under the same measurement conditions using a SiO2 film whose thickness has been measured in advance using an ellipsometer.

[0111] (Uneven color)

[0112] In order to evaluate the color unevenness of the titanium surface, the L was measured at 5 points on the front and back of the sample (1 point in the center and 4 points in the corners) after water washing treatment according to JIS Z8730:2009, for a total of 10 points. * 、a * 、b * , the color difference between each measurement point ΔE * The color difference was measured using the lightness L of each measurement point obtained in accordance with JIS Z8730:2009. * and chroma * 、b * , according to the differences ΔL between the measurement points * , Δa * , Δb * , calculated by the following formula.

[0113] Color difference ΔE * ab=[(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2 ] 1 / 2

[0114] The color difference was measured using a colorimeter CR-200b manufactured by Konica Minolta using light source C. Specifically, the color difference ΔE between each measurement point was calculated. * Samples with a maximum ab value of 5 or less were judged to have good evaluation results (OK), and the color difference ΔE * Samples whose maximum value of ab was greater than 5 were judged to have poor evaluation results (NG).

[0115] (Weather resistance)

[0116] A 50 mm L × 25 mm W × 0.3 mm T piece was cut from the water-washed sample and subjected to an accelerated discoloration test. The accelerated discoloration test was conducted by immersing the sample in a sulfuric acid aqueous solution at pH 3 at 80°C for 4 days. The L * a * b * , calculate the color difference ΔE before and after the accelerated color change test* The color difference is measured and calculated in the same way as above. The color difference ΔE is calculated by measuring the front and back sides of the sample at 1 point in the center and 4 points in the corners, and the average value of the total 10 points is used to calculate the color difference ΔE. * ab is used to evaluate weather resistance.

[0117] Due to the color difference ΔE of the color change by visual recognition * The threshold value of ab is 8.0, so the color difference ΔE before and after the accelerated color change test is * When ab is less than 8.0, the weather resistance is judged to be good (OK). The color difference ΔE before and after the color change acceleration test is * When ab was 8.0 or more, it was judged that the weather resistance was poor (NG).

[0118] (whiteness)

[0119] Furthermore, the L * 、a * 、b * , and L before cleaning process * The whiteness was evaluated by comparing the two. The measurement positions of whiteness were the same as above, and the front and back surfaces of the sample were measured at 1 point in the center and 4 points in the corners. The L was calculated by taking the average value of the total 10 points. * Used for evaluation of whiteness.

[0120] Since the L of the sample before the cleaning process * (whiteness) is about 65, so the whiteness that can be clearly recognized by vision compared with the sample before the cleaning process is used as the evaluation standard. * Samples with a value of 70 or above were judged to be good (OK), and L * Samples with a value less than 70 were judged to be poor (NG) in the evaluation results. The results are shown in Table 3. It should be noted that "-" in Table 3 indicates that it is below the detection limit. In addition, in the XPS analysis and surface oxide film columns in Table 3, the underlined conditions indicate conditions outside the scope of the present invention, and in the weather resistance, color unevenness and whiteness columns in the table, the underlined values ​​indicate that the evaluation results are NG.

[0121] [Table 3]

[0122]

[0123] As shown in Tables 2 and 3, when the chemical composition of the surface of the titanium material was analyzed by XPS method, the titanium material with Zn: 0.1 atomic % or more and Ca: 0.5 atomic % or more, and C: 20.0 atomic % or less and F: 5.0 atomic % or less as the composition of the surface oxide film had good weather resistance. Furthermore, the color unevenness and whiteness L of the sample with a surface oxide film thickness of 5 to 20 nm were * The evaluation results were all good.

[0124] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to these examples. Anyone with common knowledge in the technical field to which the present invention belongs can obviously think of various variations or modifications within the scope of the technical ideas described in the claims, and these should of course be understood to belong to the technical scope of the present invention.

Claims

1. A titanium material, characterized in that: When the chemical composition of the surface is analyzed by X-ray photoelectron spectroscopy, the surface composition contains Zn: 0.1 atomic % or more and 1.0 atomic % or less, and Ca: 0.5 atomic % or more and 1.5 atomic % or less, And as the composition of the surface oxide film, C: 20.0 atomic % or less, and F: 5.0 atomic % or less.

2. The titanium material according to claim 1, wherein: The thickness of the surface oxide film is 5 to 20 nm.

3. A method for manufacturing a titanium material, comprising a cleaning step of cleaning a titanium blank, The cleaning process comprises: The titanium blank is immersed in an aqueous solution at a temperature of 40 to 60° C. for more than 1.0 minute. The aqueous solution contains Zinc salt: 0.00030 to 0.65000 mass % calculated as Zn, Calcium salt: 0.00060 to 0.40000 mass % in terms of Ca, HF: 1.0 to 6.0 mass %, and HNO3: 4.0 to 10.0 mass %; and The water washing treatment is to wash the titanium ingot taken out from the aqueous solution with water.

4. The method for producing a titanium material according to claim 3, wherein: The zinc salt: 0.00030 to 0.00100 mass % in terms of Zn, The calcium salt is 0.00060 to 0.00108 mass % in terms of Ca.

5. The method for producing a titanium material according to claim 3 or 4, wherein: The zinc salt is ZnCl2.

6. The method for producing a titanium material according to claim 3 or 4, wherein: The calcium salt is CaCl2.

7. The method for producing a titanium material according to claim 5, wherein: The calcium salt is CaCl2. 8 . The method for producing a titanium material according to claim 3 , further comprising a heating step of heating the titanium material after the cleaning step to 300 to 900° C. in an inert atmosphere. 9 . The method for producing a titanium material according to claim 5 , further comprising a heating step of heating the titanium material after the cleaning step to 300 to 900° C. in an inert atmosphere. 10 . The method for producing a titanium material according to claim 6 , further comprising a heating step of heating the titanium material after the cleaning step to 300 to 900° C. in an inert atmosphere. 11 . The method for producing a titanium material according to claim 7 , further comprising a heating step of heating the titanium material after the cleaning step to 300 to 900° C. in an inert atmosphere.

Citation Information

Patent Citations

  • Titanium hardly generating color change in atmospheric environment and manufacturing method therefor

    JP2002012962A

  • Pure titanium material for building material and its manufacturing method

    JP2004300569A

  • Titanium less liable to be discolored in atmospheric environment

    JP2005154882A

  • Insurance management server, service providing system, and service providing method

    JP2020155144A

  • Chemical conversion treatment solution for titanium or titanium alloy and surface treatment by using the same

    JP1996158063A